NEXUS OF GREEN TECHNOLOGY AND GREEN ENERGY IN CLEAN WATER PRODUCTION AT ZERO CARBON EMISSION: AN EXPERIMENTAL STUDY - Shahidul, Islam; Ahmad Adzlan, Fadzli Khairi; Hishammudin Afifi, Huspi (Publications International Lahore, Pakistan, 2024)
This paper reports an experimental finding that was conducted with green technology and green energy for optimize clean water production instream water at zero carbon emission (CO2eq = 0). Required experimental run was estimated by using central composed design (CCD) model. Experimental data were analysed by statistical tools for achieving research objective. The experimental rig was developed with renewable granular biomass filter (RBF) and was operated at various feed pressure and flow rate. The finding revealed that the optimum pressure head 2.1 meter was required to produce required clean water quality (TSS≤ 0.8 mgL-1) at 91.0% TSS separate efficiency. It was also found that the optimum clean water production rate was 1.0 m3(hr-m2)-1] at TSS density in the product water 0.8 mgL-1. The entire water filtration process was conducted with green energy, in that aspect, clean water production was at zero carbon emission. These findings could be a reference to the water industry, engineering professionals and policy implementing agencies involved in reducing carbon emission for mitigating climate change. This study concludes that green technological nexus with green energy for producing clean water is a potential route to reducing carbon emission for mitigating climate change, and thus, economic and environmental sustainability could be achieved.